ILC2s regulate a fibroblast progenitor niche in the pancreas - Thomas Yip; Julie Stockis; Charlotte Simpson; Erika E. McCartney; Shwetha Raghunathan; Martha M. Rangel-Sosa; Sydney N. Hummel; Julia Moreno-Vicente; Gianmarco Raddi; Celine Garcia; Rugile Linkute; Silvain Pinaud; et al. (Science, 2026)
Local fibroblast development and densities influence organ health and disease, although it remains unclear how tissue fibroblast topography is controlled in situ. Here, we defined Group 2 innate lymphoid cells (ILC2s) as key regulators of fibroblast homeostasis in the pancreas. ILC2s colocalized with fibroblasts expressing the genes Pi16 + Dpp4 + Ly6c + in an interstitial niche of the exocrine pancreas, which encapsulates the organ parenchyma. ILC2s specifically regulated the expansion of Pi16 + Dpp4 + Ly6c + fibroblasts, which have progenitor capacity, while restraining differentiated intraparenchymal Col15a1 + fibroblasts during inflammation. These circuits reinforced fibroblast numbers after injury and set an inflammatory threshold. The ILC2 and Pi16 + Dpp4 + Ly6c + fibroblast progenitor niche expanded around tumors and controlled cancer-associated fibroblast ontogeny and density. Hence, ILC2-fibroblast dialogue represents a regulatory node that locally orchestrates tissue homeostasis and pathology.